Human Rights Constitutionalism in Indonesiaâs Foreign Policy - P. Wiratraman, Herlambang (The Constitutional Court of the Republic of Indonesia, 2015)
This article examines conceptual discourse of human rights constitutionalism as fundamental part of making policies in international relations. There are two key questions, first, to what extent human rights constitutionalism has been brought into discourse of its foreign policies, and second, how such human rights constitutionalism has been shaped by various actors, state and non stateâs relations. The politics of imageâ has been developed from regime to regime. However, such politics does not reflect substantially in progressing of human rights development. As part of democratic governance, and in the context of a more globalized society, Indonesia should rethink of its foreign policy foundations, especially in terms of transnational issues such as human rights, environment, and poverty. Therefore, central discussion in this regards is how to strengthen human rights constitutionalism is not merely internal and/or domestic affairs, but also this should build stronger and brave policies to develop and prioritize humanity values throughout international relations.